The Effectiveness of Peer Counseling in Addressing Cyberbullying Among Students in Islamic Boarding School - Aqillah, Hawwa Nasywa; Suhaemi, Kholid; Monalisa, Monalisa (Bulletin of Counseling and Psychotherapy, 2025)
This study aims to test the effectiveness of peer counseling guidance in reducing cyberbullying behavior among students at the Daar El Syahid Teluknaga Islamic Boarding School, Indonesia. This study used an experimental method with a pretest-posttest control group design. The research sample was selected using a purposive sampling technique, with 150 students from a population of 500. The sample was divided into an experimental group, which received peer counseling guidance intervention, and a control group, which received intervention as usual. The research instruments used included the Cyberbullying Behavior Scale, Peer Counseling Effectiveness Questionnaire, Observation Guide, and Interview. Data analysis was carried out using an independent t-test, first testing the assumptions of normality and homogeneity of variance using Kolmogorov-Smirnov or Shapiro-Wilk and Levene's Test. The study showed a significant difference between the experimental and control groups after the intervention, with a substantial decrease in cyberbullying behavior in the experimental group. The results of this study indicate that peer counseling guidance effectively reduces cyberbullying behavior among students. The program successfully raised awareness of the negative impacts of cyberbullying, developed coping strategies, and strengthened empathy and digital ethics among students. The results of this study are expected to be the basis for developing counseling programs in educational institutions to create a safer and more inclusive environment for students.